2017
DOI: 10.18632/oncotarget.22681
|View full text |Cite
|
Sign up to set email alerts
|

Targeting chaperonin containing TCP1 (CCT) as a molecular therapeutic for small cell lung cancer

Abstract: Identifying new druggable targets is desired to meet the needs for effective cancer treatments. To this end, we previously reported the efficacy of a therapeutic peptide called CT20p that displays selective cytotoxicity through inhibition of a multi-subunit, protein-folding complex called Chaperonin-Containing TCP-1 (CCT). To investigate the role of CCT in cancer progression, we examined protein levels of CCT subunits in liver, prostate, and lung cancer using human tissue microarrays. We found that these cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 65 publications
4
64
0
Order By: Relevance
“…The goal of this study is to determine whether the contribution of CCT chaperonin complex to carcinogenesis can be elucidated by focusing on a single subunit, CCT2. We and others showed that CCT2 is increased in breast, prostate, and lung cancer as compared to normal tissues and that CT20p directly interacts with CCT2 [14][15][16]21 . But whether CCT2 is an essential component of the chaperonin's activity in cancer cells and promotes tumorigenesis is unknown.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…The goal of this study is to determine whether the contribution of CCT chaperonin complex to carcinogenesis can be elucidated by focusing on a single subunit, CCT2. We and others showed that CCT2 is increased in breast, prostate, and lung cancer as compared to normal tissues and that CT20p directly interacts with CCT2 [14][15][16]21 . But whether CCT2 is an essential component of the chaperonin's activity in cancer cells and promotes tumorigenesis is unknown.…”
mentioning
confidence: 69%
“…another class of protein-folding complexes, called chaperonins, gained interest with the recognition that cancer cells highly express these mediators of protein-folding [14][15][16][17][18][19][20][21][22][23] . The cytosolic, eukaryotic chaperonin-containing TCP-1 (CCT) is an emerging player in neoplastic transformation with potential for development as a novel diagnostic marker and therapeutic target.…”
mentioning
confidence: 99%
See 3 more Smart Citations